1997
DOI: 10.1101/gad.11.7.941
|View full text |Cite
|
Sign up to set email alerts
|

The family of box ACA small nucleolar RNAs is defined by an evolutionarily conserved secondary structure and ubiquitous sequence elements essential for RNA accumulation.

Abstract: Eukaryotic cells contain a large number of small nucleolar RNAs (snoRNAs).A major family of snoRNAs features a consensus ACA motif positioned 3 nucleotides from the 3' end of the RNA. In this study we have characterized nine novel human ACA snoRNAs (U64-U72). Structural probing of U64 RNA followed by systematic computer modeling of all known box ACA snoRNAs revealed that this class of snoRNAs is defined by a phylogenetically conserved secondary structure. The ACA snoRNAs fold into two hairpin structures connec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
394
1
2

Year Published

1999
1999
2010
2010

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 319 publications
(403 citation statements)
references
References 72 publications
6
394
1
2
Order By: Relevance
“…The yeast strains used in this study are derivatives of BMA41 (MAT a/a leu2-3,112/leu2-3,112 his3-11,15/his3-11,15 ade2-1/ade2-1 ura3-1/ura3-1 trp1⌬/trp1⌬ can1-100/can1-100 ): BMA41-1a (as BMA41 but MAT a; haploid strain referred to in this work as wild type or WT); BMS1/⌬bms1 (as BMA41 but BMS1/bms1::TRP1); GAL::bms1 (as BMA41-1a but UAS GAL1 P CYC1 -BMS1 TRP1); BMS1-HA (as BMA41-1a but BMS1-HA LEU2); BMS1-ProtA (as BMA41-1a but BMS1-CBP-ProtA TRP1-Kl ); RCL1-ProtA (as BMA41-1a but RCL1-ProtA URA3-Kl; Billy et al+, 2000)+ Strain BMS1/⌬bms1 was constructed by transforming the BMA41 strain with a DNA fragment containing TRP1 gene as a selection marker with flanks complementary to the immediate upstream and downstream noncoding regions of BMS1+ The DNA was amplified by PCR using appropriate oligonucleotides as primers and plasmid pFL35 (Bonneaud et al+, 1991) as a template+ Other strains were constructed by transforming the BMA41-1a strain with a DNA fragment amplified by PCR using appropriate oligonucleotides as primers and plasmids (indicated in parentheses) as templates: GAL::bms1 (YIpGUR; Jenny et al+, 1996), BMS1-HA (pYX242, Novagen), BMS1-ProtA (pBS1479; Rigaut et al+, 1999)+ In the latter strain Bms1p is C-terminally fused with two consecutive tags, calmodulin binding peptide (CBP) and Protein A (jointly referred to as TAP-tag; see Rigaut et al+, 1999)+ Strains LSM3-ProtA (Salgado-Garrido et al+, 1999), IMP3-HA, and GAL::imp3 (Lee & Baserga, 1999) and ProtA-NOP1 (Ganot et al+, 1997) were kindly provided by B+ Seraphin, S+ Baserga, T+ Kiss, and M+ Caizergues-Ferrer+ Genetic manipulations and preparation of standard yeast media followed established procedures (Brown & Tuite, 1998)+ YPGal medium was supplemented with 20 mg/mL adenine when used for growth of strains auxotrophic for adenine+ YPD medium enriched in glucose (6%), referred to as YPD6%, was used for all experiments involving depletion of Bms1p and Imp3p in strains GAL::bms1 and GAL::imp3, respectively, to ensure maximum repression of the promoter in the GAL::bms1 allele+ This medium was also supplemented with 20 mg/mL adenine+…”
Section: Strains Media and Genetic Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The yeast strains used in this study are derivatives of BMA41 (MAT a/a leu2-3,112/leu2-3,112 his3-11,15/his3-11,15 ade2-1/ade2-1 ura3-1/ura3-1 trp1⌬/trp1⌬ can1-100/can1-100 ): BMA41-1a (as BMA41 but MAT a; haploid strain referred to in this work as wild type or WT); BMS1/⌬bms1 (as BMA41 but BMS1/bms1::TRP1); GAL::bms1 (as BMA41-1a but UAS GAL1 P CYC1 -BMS1 TRP1); BMS1-HA (as BMA41-1a but BMS1-HA LEU2); BMS1-ProtA (as BMA41-1a but BMS1-CBP-ProtA TRP1-Kl ); RCL1-ProtA (as BMA41-1a but RCL1-ProtA URA3-Kl; Billy et al+, 2000)+ Strain BMS1/⌬bms1 was constructed by transforming the BMA41 strain with a DNA fragment containing TRP1 gene as a selection marker with flanks complementary to the immediate upstream and downstream noncoding regions of BMS1+ The DNA was amplified by PCR using appropriate oligonucleotides as primers and plasmid pFL35 (Bonneaud et al+, 1991) as a template+ Other strains were constructed by transforming the BMA41-1a strain with a DNA fragment amplified by PCR using appropriate oligonucleotides as primers and plasmids (indicated in parentheses) as templates: GAL::bms1 (YIpGUR; Jenny et al+, 1996), BMS1-HA (pYX242, Novagen), BMS1-ProtA (pBS1479; Rigaut et al+, 1999)+ In the latter strain Bms1p is C-terminally fused with two consecutive tags, calmodulin binding peptide (CBP) and Protein A (jointly referred to as TAP-tag; see Rigaut et al+, 1999)+ Strains LSM3-ProtA (Salgado-Garrido et al+, 1999), IMP3-HA, and GAL::imp3 (Lee & Baserga, 1999) and ProtA-NOP1 (Ganot et al+, 1997) were kindly provided by B+ Seraphin, S+ Baserga, T+ Kiss, and M+ Caizergues-Ferrer+ Genetic manipulations and preparation of standard yeast media followed established procedures (Brown & Tuite, 1998)+ YPGal medium was supplemented with 20 mg/mL adenine when used for growth of strains auxotrophic for adenine+ YPD medium enriched in glucose (6%), referred to as YPD6%, was used for all experiments involving depletion of Bms1p and Imp3p in strains GAL::bms1 and GAL::imp3, respectively, to ensure maximum repression of the promoter in the GAL::bms1 allele+ This medium was also supplemented with 20 mg/mL adenine+…”
Section: Strains Media and Genetic Methodsmentioning
confidence: 99%
“…Immunoprecipitations were performed as previously described (Ganot et al+, 1997)+ Buffers contained either 500 mM potassium acetate (for IP of RNA) or 250 mM sodium chloride (for IP of proteins) during binding and washing steps+…”
Section: Immunoprecipitationsmentioning
confidence: 99%
“…Structure of the 35S pre-rRNA and the pre-rRNA processing pathway in Saccharomyces cerevisiae+ A: In the 35S primary transcript, the sequences of the mature 18S, 5+8S, and 25S pre-rRNAs are embedded in the external transcribed spacers (59 and 39 ETS) and in the internal transcribed spacers (ITS1 and ITS2)+ The cleavage sites are indicated by uppercase letters (A 0 to E); the oligonucleotides probes used are indicated by lowercase letters (a to g)+ B: Successive cleavage of the 35S pre-rRNA at sites A 0 and A 1 generates the 33S and 32S pre-rRNAs+ Cleavage of the 32S pre-rRNA at site A 2 then generates the 20S and 27SA 2 pre-rRNAs, which are precursors to the RNA components of the small and large ribosomal subunits, respectively+ The mature 18S rRNA is generated by cleavage of the 20S pre-rRNA at site D+ The 27SA 2 precursor is either cleaved at site A 3 by RNase MRP generating the 27SA 3 prerRNA, or at site B 1L to yield 27SB L pre-rRNA+ The 27SA 3 pre-rRNA is rapidly digested by the 59 to 39 exonucleases Xrn1p and Rat1p to yield the 27SB S pre-rRNA+ Processing at site B 2 , the 39 end of the 25S rRNA, is thought to occur while the 59 ends of the 27SB prerRNAs are generated+ The 27SB S and 27SB L pre-rRNAs both follow the same pathways of processing to 25S and 5+8S S/L through cleavage at sites C 1 , the 59 mature end of the 25S rRNA, and C 2 in ITS2 followed by 39 to 59 exonucleolytic digestion of 7S S and 7S L from site C 2 to E by the exosome complex+ The early pre-rRNA cleavages at sites A 0 , A 1 , and A 2 require the box CϩD snoRNAs U3 and U14, as well as Nop58p+ et al+, 1997)+ This construct was expressed in a deleted nop58-⌬ background and shown to be fully functional (Gautier et al+, 1997)+ Immunoprecipitation of ProtA-Nop58p with IgGagarose beads resulted in the coprecipitation of all tested box CϩD snoRNAs: U3, U14, U18, U24, snR4, snR13, and snR190 (Fig+ 2A, lanes 4-6 and data not shown)+ The experiment was performed at two salt concentrations: 150 mM KAc (Fig+ 2A-C, lanes 4-6) and 500 mM KAc (data not shown)+ The HϩACA snoRNAs were reported to coprecipitate nonspecifically with Nop1p at 150 mM salt but not in the more stringent conditions of 500 mM KAc (Ganot et al+, 1997b)+ Coprecipitation of the box CϩD snoRNAs with Nop58p was observed at both salt concentrations+ No precipitation of any RNA was seen with an otherwise isogenic NOP58 strain expressing only nontagged Nop58p (Fig+ 2A-C, lanes 1-3)+ Nop58p bears a highly charged, carboxyl KKD/E repeat domain that is also present in other nucleolar proteins (Gautier et al+, 1997;Weaver et al+, 1997;Lafontaine et al+, 1998a)+ This domain was previously shown to be dispensable both for the nucleolar localization of Nop58p and for its association with Nop1p (Gautier et al+, 1997)+ To test for the potential involvement of the KKD/E repeats in snoRNA association, we used a construct in which a stop codon was introduced by site-directed mutagenesis in the NOP58 coding region upstream of the KKD/E motif (Gautier et al+, 1997)+ This resulted in the expression of a fusion protein lacking the carboxy-terminal domain+ The CϩD snoRNAs were recovered with similar efficiency using this construct or the full-length ProtA-fusion protein (Fig+ 2A, lanes 7-12)+ The association of ProtA-Nop58p⌬KKD/E with the snoRNAs was unaltered at salt concentrations of 150 mM or 500 mM KAc (Fig+ 2A, compare lanes 7-9 with 10-12)+ With either ProtA-Nop58p or ProtA-Nop58p⌬KKD/E little coprecipitation was observed for the box HϩACA snoRNAs tested: snR3, snR10, snR...…”
Section: Nop58p Is Specifically Associated With the Box C+d Snornasmentioning
confidence: 97%
“…Eukaryotic ribosomal RNAs (rRNAs) are synthesized from precursor rRNAs (pre-rRNAs) through a complex processing pathway (Fig+ 1; see Eichler & Craig, 1994;Venema & Tollervey, 1995;Sollner-Webb et al+, 1996;Tollervey, 1996 for recent reviews)+ While these processing reactions take place, the pre-rRNAs are covalently modified on both the sugar residues (29-O-methylation) and bases (pseudouridine formation and base methylation) (Maden, 1990;Maden & Hughes, 1997) and assemble with the ribosomal proteins into ribonucleoprotein (RNP) particles (Warner, 1989;Raué & Planta, 1991)+ Most of these steps occur in the nucleolus, a specialized subnuclear compartment (Reeder, 1990;Hernandez-Verdun, 1991;Mélèse & Xue, 1995)+ Eukaryotic nucleoli contain a large number of small, metabolically stable RNAs known collectively as the small nucleolar RNAs (snoRNAs) (reviewed in Fournier & Maxwell, 1993;Bachellerie et al+, 1995;Maxwell & Fournier, 1995); some 150 snoRNA species are predicted to be present in human cells+ Recently, it has become apparent that these snoRNAs fall into two classes that are structurally and functionally distinct (Balakin et al+, 1996;Ganot et al+, 1997b;Tollervey & Kiss, 1997;reviewed in Lafontaine & Tollervey, 1998)+ These are designated the box CϩD and the box HϩACA snoRNAs after conserved sequence elements that are believed to be sites of RNA-protein interactions+ The only exception is the RNA component of the endonuclease RNase MRP, which is related to RNase P (Forster & Altman, 1990;Lygerou et al+, 1994; reviewed in Morrissey & Tollervey, 1995)+ Within each major family of snoRNAs, two functionally distinct groups can be discerned+ A small number of snoRNA species-the box HϩACA snoRNA snR30 and the box CϩD snoRNAs U3 and U14-are required for cleavage of the pre-rRNA at the early processing sites, A 0 , A 1 , and A 2 (Fig+ 1; Li et al+, 1990;Hughes & Ares, 1991;Morrissey & Tollervey, 1993)+ Since these cleavages are required for synthesis of the 18S rRNA, this group of snoRNAs are essential for viability+ In contrast, the vast majority of snoRNAs function as guide RNAs for the covalent modification of the pre-...…”
Section: Introductionmentioning
confidence: 99%
“…In eukaryotes, the tandemly repeated ribosomal genes are cotranscribed as a single pre-rRNA precursor molecule by RNA polymerase I in the nucleolus+ During or immediately after transcription of the pre-rRNA, the sequences that will be incorporated into the mature ribosomes are extensively chemically modified, the two most numerous modifications being 29O-ribose methylations and pseudouridylations (Maden, 1990)+ In addition to the sequences retained in the mature rRNA species (18S, 5+8S, and 25S/28S), the primary transcript contains two external and two internal transcribed spacers (respectively 59 and 39 ETS, ITS1, and ITS2) that are excised through a complex series of endonucleolytic and exonucleolytic cleavages [for review, see Venema & Tollervey (1999) and Fig+ 1 for a cartoon of pre-rRNA processing steps]+ snoRNPs (small nucleolar ribonucleoprotein particles), which consist of snoRNAs (small nucleolar RNAs) associated with proteins, are required in trans for the modification and/or cleavage reactions of the prerRNA+ A large number of snoRNAs are known, most of which can be divided in two families on the basis of common structural and consensus sequence motifs [for review, see Balakin et al+ (1996); Smith & Steitz (1997); Tollervey & Kiss (1997)]+ The first family is composed of snoRNAs sharing the so-called C and D boxes (Bachellerie & Cavaillé, 1998)+ The second family consists of snoRNAs that share a common hairpin-hinge-hairpintail structure and the H and ACA boxes, located, respectively, in the hinge and the tail (Balakin et al+, 1996;Ganot et al+, 1997b)+ Only a few snoRNAs belonging to these families are required for pre-rRNA cleavage events+ In yeast, the U3 and U14 C/D snoRNAs as well as the snR10 and snR30 H/ACA snoRNAs are involved in early cleavage events necessary for 18S rRNA production (Tollervey, 1987;Li et al+, 1990;Hughes & Ares, 1991;Morrissey & Tollervey, 1993)+ The other members of both families function as pre-rRNA modification guides, selecting by base-pairing interactions with the pre-rRNA ribose moieties that will undergo 29O methylation in the case of C/D snoRNAs (Cavaillé et al+, 1996;Kiss-Laszlo et al+, 1996;Tycowski et al+, 1996) or uridine residues to be converted to pseudouridines in the case of H/ACA snoRNAs (Ganot et al+, 1997a;Ni et al+, 1997)+ Since the discovery that most C/D and H/ACA snoRNAs function as modification guides, interest has FIGURE 1. Structure of the pre-rRNA and processing pathway in Saccharomyces cerevisiae.…”
Section: Introductionmentioning
confidence: 99%